System and method for accessing document data via a web service - ANGLE THOMAS; MOLLOY ROBERT; BLAZEJEWSKI EDWARD; KENNEY JOSEPH; KUO CHAO-HEN; DICK ANDREA (2006)
A method for accessing document data via a web service is disclosed which includes receiving a request from a client application. The request for document data to be retrieved from a repository managed by an IDARS/DOM application. The method also includes processing the request including creating and transmitting at least one access request to the IDARS/DOM application, and receiving document data in response to each transmitted access request. The method further includes formatting the document data received from the IDARS/DOM application. The method still further includes transmitting the formatted document data to the client application. Apparatus, systems and articles of manufacture for accessing document data via a web service are also disclosed.